2017
DOI: 10.1186/s12929-017-0330-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a high-throughput calcium mobilization assay for the orphan receptor GPR88

Abstract: BackgroundGPR88 is an orphan G protein-coupled receptor highly expressed in the striatum and is implicated in basal ganglia-associated disorders. However, the receptor functions of GPR88 are still largely unknown due to the lack of potent and selective ligands appropriate for central nervous system investigation. Development of a high-throughput screening assay for GPR88 should facilitate the discovery of novel ligands to probe GPR88 functions.MethodsIn this paper, we describe the development of a CHO-Gαqi5-GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…24 Later, we observed that, over time, the HEK293 cells were physically unhealthy after transfection with GPR88 and subsequently led to deteriorated responses to 2-PCCA. 26 To facilitate the SAR study, we recently created a stable CHO-PPLS-HA-GPR88 cell line and measured cAMP levels using the PerkinElmer Lance assay kit. 27 The new assay system is reliable and sensitive and therefore was used in subsequent SAR studies.…”
Section: Resultsmentioning
confidence: 99%
“…24 Later, we observed that, over time, the HEK293 cells were physically unhealthy after transfection with GPR88 and subsequently led to deteriorated responses to 2-PCCA. 26 To facilitate the SAR study, we recently created a stable CHO-PPLS-HA-GPR88 cell line and measured cAMP levels using the PerkinElmer Lance assay kit. 27 The new assay system is reliable and sensitive and therefore was used in subsequent SAR studies.…”
Section: Resultsmentioning
confidence: 99%
“…Because the NPFF1 assay was originally developed in 96-well format, we miniaturized the assay to 384-well format and determined the cell density that provided a confluent cell monolayer and NPFF potency/efficacy consistent with the 96-well assay. We then tested the calcium mobilization assay using our automated liquid handling equipment, which includes a Biotek cell dispenser, Beckman Coulter Biomek NX, and FLIPR Tetra to determine whether automation resulted in adverse effects; no changes in assay performance were observed . Using the automated and miniaturized assay, we generated a Z ′-factor by testing positive (10 μM final NPFF) and negative controls (1% DMSO/assay buffer) on three individual days .…”
Section: Resultsmentioning
confidence: 99%
“…We then tested the calcium mobilization assay using our automated liquid handling equipment, which includes a Biotek cell dispenser, Beckman Coulter Biomek NX, and FLIPR Tetra to determine whether automation resulted in adverse effects; no changes in assay performance were observed. 43 Using the automated and miniaturized assay, we generated a Z′-factor by testing positive (10 μM final NPFF) and negative controls (1% DMSO/assay buffer) on three individual days. 44 The Z′-factor (N = 3) was determined to be 0.75 with a standard deviation of 0.06; a Z′-factor greater than 0.5 is considered appropriate for HTS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 Since then, our group has developed numerous calcium mobilization assays for multiple targets and found that pretreating cells for 15 min prior to compound addition and simultaneous data acquisition dramatically reduces the initial cellular response to DMSO. [35][36][37][38] Thus, when this pretreatment protocol was applied to the hTAAR1 assay during the initial development stage, a concentration of 1% DMSO did not elevate the baseline (baseline RFU = 243 for 1% DMSO, compared with 250 RFU for 0% DMSO).…”
Section: -Well Assay Miniaturizationmentioning
confidence: 94%